The Effect Of Probing Prompting Learning Approach And Learning Motivation On Students' Science Learning Outcomes In Grade VII SMPN 31 Seluma - Jayadi, Bangkit; S, Sukarno; K, Khosi’in (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The formulation of the problem in this research is first, there is an influence of the probing prompting learning approach on the science learning outcomes of Class VII Students at SMPN 31 Seluma. Second, there is an influence of learning motivation on the science learning outcomes of class VII students at SMPN 31 Seluma. Third, there is an influence of the probing prompting learning approach and learning motivation on the science learning outcomes of class VII students at SMPN 31 Seluma. The type of research in this research is quantitative research using quasi-experimental or quasi-experimental methods. This design uses control and experimental groups. The results of the first research, there is a probing prompting learning approach to the science learning outcomes of Class VII students at SMPN 31 Seluma. Second, there is an influence of learning motivation on student learning outcomes in science learning outcomes for Class VII students at SMPN 31 Seluma. Third, there is a simultaneous influence of the probing prompting learning approach and learning motivation on the science learning outcomes of class VII at students at SMPN 31 Seluma. Keywords: Probing Prompting Learning Approach, Learning Motivation, Learning Outcomes.